Taking the EEG Back Into the Brain: The Power of Multiple Discrete Sources - Scherg, Michael; Berg, Patrick; Nakasato, Nobukazu; Beniczky, Sándor (Frontiers in Neurology, 2019)
Background: In contrast to many neuroimaging modalities, clinical interpretation of EEG does not take advantage of post-processing and digital signal analysis. In most centers, EEG is still interpreted at sensor level, exactly as half a century ago. A major task in clinical EEG interpretation is the identification of interictal epileptiform discharges (IEDs). However, due to overlap with the background activity, IEDs can be hard to detect in the scalp EEG. Since traditional montages, like bipolar and average reference, are linear transformations of the recorded channels, the question is, whether we can provide linear transformations of the digital EEG to take it back into the brain, at least on a macroscopic level. The goal is to make focal epileptiform activities better visible and separate most of the overlap. Methods: Multiple discrete sources provide a stable linear inverse to transform the EEG into source space with little cross-talk between source regions. The model can be based on a few dipoles or regional sources adapted to the individual EEG and MRI data or on few standard sources evenly distributed throughout the brain, e.g. below the 25 EEG standard electrodes. Results: Auditory and somatosensory evoked potentials serve as teaching examples to show how various source spaces can reveal the underlying source components including their loss or alteration due to lesions. Source spaces were able to reveal the propagation of source activities in frontal IEDs and the sequential activation of the major nodes of the underlying epileptic network in myoclonic epilepsy. The power of multiple discrete sources in separating the activities of different brain regions could also be demonstrated for the ongoing EEG in cases with frontal cortical dysplasia and bitemporal lobe epilepsy as the new source space 25 made IEDs more clearly visible over the EEG background signals. The more focal nature of source versus scalp space was quantitatively confirmed using a new measurement of focality. Conclusion: Multiple discrete sources have the power to transform the EEG back into the brain by defining new EEG traces in source space. Using standard source space 25, these can serve for improved clinical interpretation of EEG.